An overview: multiscale simulation in understanding the radiation damage accumulation of reactor materials. (October 2021) - Chen, Dandan; He, Xinfu; Chu, Genshen; He, Xiao; Jia, Lixia; Wang, Zhaoshun; Yang, Wen; Hu, Changjun
The reactor is an extreme environment of high temperature, high pressure, and high radiation dose. Damage accumulates in structural materials over service time. It will eventually lead to material failure, such as hardening, embrittlement, and swelling. The radiation damage accumulation is an inherent, complex, and multiscale process, which has been studied extensively with multiscale modeling and simulation methods. The rapid development of high-performance computing makes it possible to accurately operate multiscale simulation for the microstructure evolution of irradiated reactor materials. The European Union, the USA, and China have put great effort into this, and many related works have been carried out. This paper first outlines the basic application of multiscale modeling and simulation technology in understanding the effects of radiation on reactor structural materials. Then, some relevant projects carried out by the USA, the European Union, and China in recent years are summarized. Next, the paper focuses on three widely used simulation techniques at different scales: molecular dynamics, kinetic Monte Carlo, and cluster dynamics. For each method, some key developments in algorithms and computer implementations are reviewed. Finally, the comparison between them is discussed.